Reduplikasi Bahasa Melayu Riau Subdialek Pangean - Aulia, Niken; Charlina, Charlina; Septyanti, Elvrin (GERAM: Gerakan Aktif Menulis, 2023)
This research aims to identify the form and meaning of reduplication in the Riau Malay language, the Pangean subdialect. This research is descriptive research with data collection techniques by fishing, listening, engaging, speaking, recording, and taking notes. The data analysis technique used is listening again to the recording during the research, then continuing to present the data, and drawing conclusions from the analysis that has been carried out on the data. Based on the research results, 103 data were obtained with the classification of full form reduplication, partial form, affixed form, and phoneme change form. As for meaning, namely stating many meanings, stating unconditional meaning, stating similar meanings, stating that actions are carried out repeatedly, stating that actions are done at will, stating that actions are carried out by two parties regarding each other, stating things related to work, stating somewhat meaning, expressing the highest level meaning, expressing the meaning of intensity of feeling.